2017
DOI: 10.15361/1984-5529.2017v45n3p271-277
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of fruits of strawberry cultivars in an organic production system

Abstract: Most works on strawberry refer to conventional production systems and in traditional regions, so there is little scientific knowledge for its cultivation in other conditions, such as in the organic production of northwestern RS, Brazil. The objective of this work was to evaluate the productive aspects and physicochemical characteristics of strawberry cultivars grown in an organic production system in the northwest of RS. The experiment was carried out at the Cerro Largo Campus of the Federal University of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Biological traits exhibited by certain fungal isolates with their host plant and their environment could be related to these results. 63 Regarding plant cultivars, it has already been reported that different strawberry cultivars showed significant differences in quality and yield, 64 highlighting the importance of testing specific responses of different cultivars to draw conclusions on growth promotion potential.…”
Section: Discussionmentioning
confidence: 99%
“…Biological traits exhibited by certain fungal isolates with their host plant and their environment could be related to these results. 63 Regarding plant cultivars, it has already been reported that different strawberry cultivars showed significant differences in quality and yield, 64 highlighting the importance of testing specific responses of different cultivars to draw conclusions on growth promotion potential.…”
Section: Discussionmentioning
confidence: 99%